2011
DOI: 10.1590/s1807-59322011000300005
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and recurrence of acute otitis media in Taiwan's pediatric population

Abstract: OBJECTIVE:To report the incidence and recurrence of acute otitis media (AOM) in Taiwan's pediatric population.METHODS:Information from children (aged< = 12 years) with a diagnosis of AOM was retrieved from the 2006 National Healthcare Insurance claims database. We calculated the cumulative incidence rate and the incidence density rate of recurrent AOM within one year after the initial diagnosis in 2006. We used a multivariate logistic regression model to assess the predictors for recurrence of AOM.RESULTS:The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
21
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 17 publications
1
21
2
Order By: Relevance
“…This is attributed to their having shorter and more horizontal Eustachian tube, lower immunity compared to adults and the fact that bacteria adhere better to epithelial cells of young children than adults [7]. The males had a significantly (P < 0.05) higher prevalence than females and this consistent with reports of Nwankwo and Okeke [13] and Wang et al [14]. The reason for this observation is still unknown.…”
Section: Discussionsupporting
confidence: 85%
“…This is attributed to their having shorter and more horizontal Eustachian tube, lower immunity compared to adults and the fact that bacteria adhere better to epithelial cells of young children than adults [7]. The males had a significantly (P < 0.05) higher prevalence than females and this consistent with reports of Nwankwo and Okeke [13] and Wang et al [14]. The reason for this observation is still unknown.…”
Section: Discussionsupporting
confidence: 85%
“…8 Wang et al, using the National Health Insurance (NHI) claims database of Taiwan, estimated that the age-specific annual incidence of OM was 71.7 per 1000 children aged <2 years, and 158.8 per 1000 3-to 5-yearolds, and 4.0 per 1000 children aged 6 to 12 years. 9 These data show a quite different incidence of OM among children in Taiwan as compared with other countries.…”
Section: Introductionmentioning
confidence: 73%
“…Another study in Taiwan demonstrated that a peak age incidence of AOM among children was 3 to 5 years. 9 The two questionnaire studies showed that most of children in Taiwan had their first AOM episode after infancy (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence of OM by age in Thailand, Annual AOM prevalence and AOM-related outpatient visits and hospital admissions, Singapore[104].…”
mentioning
confidence: 99%